2009
DOI: 10.1002/ps.1699
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and application of entomopathogenic nematode‐infected cadavers for control of Hoplia philanthus in turfgrass

Abstract: This study demonstrated that kaolin-starch coating provided superior protection and preservation of EPN-infected cadavers. Use of formulated cadavers may solve several current problems preventing the wider utilisation of EPNs in pest management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…To target belowground (e.g. Ansari et al 2009;Batalla-Carrera et al 2010;Shapiro-Ilan et al 2010b), as well as aboveground insect pests (e.g. Mbata and Shapiro-Ilan 2010;Batalla-Carrera et al 2010;Shapiro-Ilan et al 2010a), commercially available EPN have to be correctly applied to ensure that they reach and infect their target pest (Shapiro-Ilan et al 2006).…”
mentioning
confidence: 99%
“…To target belowground (e.g. Ansari et al 2009;Batalla-Carrera et al 2010;Shapiro-Ilan et al 2010b), as well as aboveground insect pests (e.g. Mbata and Shapiro-Ilan 2010;Batalla-Carrera et al 2010;Shapiro-Ilan et al 2010a), commercially available EPN have to be correctly applied to ensure that they reach and infect their target pest (Shapiro-Ilan et al 2006).…”
mentioning
confidence: 99%
“…Ansari et al (2009) used a kaolin-starch mixture and Del Valle et al (2009) used unflavoured gelatin; both authors demonstrated that the coating provided protection and promoted the conservation of the insect cadavers. Another alternative was developed by Shapiro-Ilan et al (2010) and Morales-Ramos et al (2013).…”
Section: Formulations For Direct Application In the Fieldmentioning
confidence: 99%
“…EPN-infected cadavers have proved to be a good alternative to the direct application of EPNs for the control of soil pests, especially on the basis of the results of Ansari et al (2009), Del Valle et al (2009, and Spence et al (2011) to solve the problem of the fragility of the cadavers. In order to obtain an optimal product, we consider necessary: increasing the survival time at room temperature, standardising the final product and evaluating these technologies with other nematode species of economic importance for crop protection.…”
Section: Formulations For Direct Application In the Fieldmentioning
confidence: 99%
“…In view of the above, we customized and adopted the relatively novel EPN-application technology of implanting H. indica-infected Galleria cadavers in the soil. The application of Galleria cadavers has shown encouraging results in the laboratory, greenhouse and field conditions 16,17 . In Brazil, this method has been used for the control of guava weevil in guava plantations 18 .…”
Section: Field Trials By Implanting Epn-infected Galleria Cadavers Inmentioning
confidence: 99%